Bilateral Relations Between the Russian Federation and the People’s Republic of China: Their Legal Evolution from the Second World War to the Special Military Operation - M. Mateykovich; A. Skorobogatko (BRICS Law Journal, 2023)
The relationship between the Russian Federation and the People’s Republic of China goes back more than seventy years and has undergone considerable changes over the decades. This article attempts to shed light on the evolution of the two countries’ bilateral relations over the decades, analyze the background and future of certain phenomena in those relations, such as the economic connections that exist in the Sino- Russian relations, and examine the strengthening of Moscow’s and Beijing’s ties in light of the Special Military Operation. Special attention is paid to the analysis of the treaties and agreements concluded between the two countries, with a particular focus on the documents of the post-Soviet period, while making extensive references to Russian judicial practice in the implementation of these treaties and agreements. By doing so, the article hopes to contribute to the understanding of two of the world’s most important countries’ relationship which has steadily been gaining importance on the international stage and is poised to bear strong influence on global politics in the 21 st century.